Charter and Supplemental Charter of the Hudson's Bay Company - Hudson's Bay Company (Salt Lake City, UT : Project Gutenberg, 2004)
"Charter and Supplemental Charter of the Hudson's Bay Company" is a historical legal document that outlines the foundation and governing principles of the Hudson's Bay Company, established under a royal charter in the late 17th century. Written primarily in the late 17th century and subsequently supplemented in the late 19th century, the book provides critical insights into the operations, trade, governance, and territorial rights of one of the most significant commercial enterprises of colonial North America. The text encapsulates the intricate relationship between commerce and colonial ambitions during this era. The content of the book features the original charter that incorporates the Hudson's Bay Company, granting it expansive rights to trade within and control newly discovered territories in North America. The document details the structure of the company$1 (Bs governance, including the roles of the Governor and various committees responsible for the administration of trade and legal matters. Additionally, the supplemental charter updates various provisions to align with more modern corporate regulations, including election processes and governance flexibility. Through this charter, we can discern the evolving commercial strategies and legal frameworks that facilitated the company$1 (Bs influence in the fur trade and its lasting impact on Canadian history. (This is an automatically generated summary.)s
Release date is 2004-09-01
Produced by Sean Barrett, Charles Franks
Keywords: Fur trade; Charters; Hudson's Bay Company